Tick and Tick Borne Protozoan Diseases of Livestock in the Selected Hilly Areas of Bangladesh (International Journal of Agricultural Research, Innovation and Technology, 2013)
To study the tick and tick borne protozoan diseases of livestock in the hilly areas of Bangladesh, an attempt was made to collect tick and blood samples from cattle, goat and gayal (Bos frontalis) from different areas of the three hill districts. In this study, two species of ticks namely, Boophilus microplus (92%) and Amblyomma testudinarium (21.6%) and two species of blood protozoa like Babesia bigemina (16.63%) and Anaplasma marginale (14.94%) were recorded. Seasonal prevalence of ticks was highest in summer (97%) in comparison to rainy (95%) and winter (86%) season. On the other hand, the seasonal prevalence of blood protozoa was highest in rainy season (45.45%) in comparison to summer (27.87%) and winter (16.55%). Again, animals aged more than 2 (two) years of age (52%) found to be more susceptible to blood protozoan diseases than animals aged between 1-2 years of age (33.97%). But none of the animals under one year of age were found to be infected with blood protozoan diseases. DOI: http://dx.doi.org/10.3329/ijarit.v1i1-2.13934 Int. J. Agril. Res. Innov. & Tech. 1 (1&2): 60-63, December, 2011